2017
DOI: 10.7863/ultra.16.04073
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography Imaging for the Features of Symptomatic Carotid Plaques: A Feasibility Study

Abstract: Shear wave elastography can evaluate the Young's modulus of carotid plaque stably, and could serve as an additional method for the detection of symptomatic carotid plaques, which, in combination with common ultrasound, can promote the efficiency of differentiating symptomatic carotid plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 40 publications
3
44
0
8
Order By: Relevance
“…Phantom studies have demonstrated the feasibility of Young's modulus estimates but highlight errors due to the requirement for a different wave propagation model than used by current commercial systems [418 -421]. Nevertheless, human studies show good reproducibility and potential clinical benefit [422 -426], with evidence that Young's modulus of carotid plaque correlates with qualitative (Gray-Weale scale) appearance [422,425,426] and quantitative (grayscale median) B-mode ultrasound measurements [422,426], and helps to provide improved diagnostic performance of carotid plaque vulnerability [422,426]. Studies found a lower mean Young's modulus for vulnerable plaque, although values differ (50 kPa vs. 79 kPa [426]; 62 kPa vs. 88 kPa [422]; 81 kPa vs. 115 kPa [425]).…”
Section: Swementioning
confidence: 99%
“…Phantom studies have demonstrated the feasibility of Young's modulus estimates but highlight errors due to the requirement for a different wave propagation model than used by current commercial systems [418 -421]. Nevertheless, human studies show good reproducibility and potential clinical benefit [422 -426], with evidence that Young's modulus of carotid plaque correlates with qualitative (Gray-Weale scale) appearance [422,425,426] and quantitative (grayscale median) B-mode ultrasound measurements [422,426], and helps to provide improved diagnostic performance of carotid plaque vulnerability [422,426]. Studies found a lower mean Young's modulus for vulnerable plaque, although values differ (50 kPa vs. 79 kPa [426]; 62 kPa vs. 88 kPa [422]; 81 kPa vs. 115 kPa [425]).…”
Section: Swementioning
confidence: 99%
“…Seven studies (Ramnarine et al 2014b;Garrard et al 2015;Li et al 2016;Zhang et al 2016;Alis et al 2018;Shang et al 2018;Marlevi et al 2020) did not report whether they included patients randomly or consecutively, and one study reported they did not (Marais et al 2019). In addition, most studies (Li et al 2016;Zhang et al 2016;Lou et al 2017;Marais et al 2019) did not report whether the index test was interpreted without knowledge of the reference standard and vice versa. Additionally, multiple studies (Ramnarine et al 2014b;Zhang et al 2016;Lou et al 2017;Shang et al 2018) used echogenicity as a reference standard in assessment of plaque vulnerability.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…21,22 Ramnarine et al 23 have used shear wave elastography to quantify plaque elasticity, concluding that symptomatic plaques had a significantly lower mean of Young's Modulus compared to asymptomatic plaques and that the incorporation of elastography to the degree of stenosis improved both sensitivity and specificity for the detection of vulnerable plaque. Lou et al 24 have shown that the calculation of Young's modulus with shear wave elastography has excellent reproducibility and is significantly correlated with the Gray-Weale's echogenicity classification, importantly confirming that symptomatic plaques show a lower mean Young's Modulus and the combination of Young's modulus and degree of stenosis yields a higher sensitivity and specificity for the identification of symptomatic plaques. 24 When using histology as the reference method, it was found that the mean Young's modulus was significantly lower in unstable plaques as well as those with intraplaque haemorrhage, thrombus and increased number of foam cells.…”
Section: Tissue Elastographymentioning
confidence: 89%
“…Lou et al 24 have shown that the calculation of Young's modulus with shear wave elastography has excellent reproducibility and is significantly correlated with the Gray-Weale's echogenicity classification, importantly confirming that symptomatic plaques show a lower mean Young's Modulus and the combination of Young's modulus and degree of stenosis yields a higher sensitivity and specificity for the identification of symptomatic plaques. 24 When using histology as the reference method, it was found that the mean Young's modulus was significantly lower in unstable plaques as well as those with intraplaque haemorrhage, thrombus and increased number of foam cells. 25 In the light of these results, tissue elastography appears as a promising method in the risk stratification of carotid plaques, which could be used in the future for selection of plaques more prone to the occurrence of neurologic symptoms ( Figure 5).…”
Section: Tissue Elastographymentioning
confidence: 89%